Production and performance of bio-based mineral fertilizers from agricultural waste using ammonia (stripping-)scrubbing technology. (15th April 2019) - Sigurnjak, I.; Brienza, C.; Snauwaert, E.; De Dobbelaere, A.; De Mey, J.; Vaneeckhaute, C.; Michels, E.; Schoumans, O.; Adani, F.; Meers, E.
Highlights: Products from (stripping-)scrubbing manure based flows are defined as animal manure. Nitrogen (N) in recovered (stripping-)scrubbing products is present in mineral form. Recovered N products performed similar as synthetic N fertilizer in crop trials. Legal acceptance of recovered products as fertilizers would foster manure recycling. Abstract: Development and optimization of nutrient recovery technologies for agricultural waste is on the rise. The full scale adoption of these technologies is however hindered by complex legal aspects that result from lack of science-based knowledge on characterization and fertilizer performance of recovered end-products. Ammonium sulfate (AS) and ammonium nitrate (AN), end-products of (stripping-)scrubbing technology, are currently listed by the European Commission as high priority products with the potential of replacing synthetic N fertilizers. The legal acceptance of AS and AN will be highly dependent on critical mass of scientific evidence. This study describes four different (stripping-)scrubbing pathways to recover ammonia with an aim to (i) assess product characteristics of ammonium nitrate (AN) and ammonium sulfate (AS) produced from different installations, (ii) evaluate fertilizer performance of recovered end-products in greenhouse ( Lactuca sativa L.) and full field ( Zea mays L.) scale settings and (iii) compare the observed performances with other published studies. Results have indicated that the recovered products might have a different legal status, as either mineral N fertilizer or yet as animal manure, depending on the used (stripping-)scrubbing process pathway. Nevertheless, no significant differences in respect to product characterization and fertilizer performance of AN and AS have been identified in this study as compared to the conventional use of synthetic N fertilizers. This indicates that recovered AS and AN are valuable N sources and therefore might be used as N fertilizers in crop cultivation.